2018
DOI: 10.1073/pnas.1718868115
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective measurement of coupled spin pairs in an organic semiconductor

Abstract: From organic electronics to biological systems, understanding the role of intermolecular interactions between spin pairs is a key challenge. Here we show how such pairs can be selectively addressed with combined spin and optical sensitivity. We demonstrate this for bound pairs of spin-triplet excitations formed by singlet fission, with direct applicability across a wide range of synthetic and biological systems. We show that the site sensitivity of exchange coupling allows distinct triplet pairs to be resonant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 45 publications
5
60
0
Order By: Relevance
“…Magnetic-Field Effects on the Triplet Yield. Previous studies on SF chromophores have observed magnetic-field effects (MFEs) on both fluorescence (20)(21)(22)(24)(25)(26)(27) and device performance (28). The shape of the MFE curve depends on the level-crossing mechanism of the (T 1 T 1 ) pairs and thus provides valuable information on how to tune the mixing of the various (T 1 T 1 ) states.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic-Field Effects on the Triplet Yield. Previous studies on SF chromophores have observed magnetic-field effects (MFEs) on both fluorescence (20)(21)(22)(24)(25)(26)(27) and device performance (28). The shape of the MFE curve depends on the level-crossing mechanism of the (T 1 T 1 ) pairs and thus provides valuable information on how to tune the mixing of the various (T 1 T 1 ) states.…”
Section: Resultsmentioning
confidence: 99%
“…66 Another emerging technique for probing the role of m (T 1 T 1 ) in SF is time-resolved electron spin resonance (tr-ESR). 40,67,68 This technique has recently been used to directly interrogate m (T 1 T 1 ) in films of TIPS-tetracene or solutions of bipentacene. 13,14 In this experiment, an optical pulse populates excited states that evolve in time, and transiently populated paramagnetic species are probed by a continuous wave microwave source.…”
Section: (T 1 T 1 ) Revealed By a Variety Of Spectroscopic Techniquesmentioning
confidence: 99%
“…We consider that the distinct spectral feature at 720 nm could be due to a specific geometric orientation of a pair of TTBP molecules. It has been shown in TIPS-tetracene that emission from triplet pairs with strong exchange coupling is red-shifted relative to that of weak coupling 45 , so this feature could be attributed to very strongly coupled pairs. This would likely originate in pairs of molecules that are slip-stacked face-to-face at only 0.35 nm, consistent with the crystal structures reported by Müller et al 35 , notably closer than any pair in the TIPS-tetracene crystal structure 45 .…”
Section: Resultsmentioning
confidence: 99%